Effect of the intrinsic and extrinsic factors on the growth and development of young foals under subtropical conditions of Pakistan. - Muhammad Athar Chatha; Nisar Ahmad; Muhammad Athar Abbas; Muhammad Saadullah; Jawaria Ali Khan (PLoS ONE)
This study was designed to explore the impact of intrinsic (breed of foal, age of dam, and age of foal at weaning) and extrinsic (season of birth and housing type) factors on the growth and survival of foals in the subtropical conditions of Pakistan. For the growth study, retrospective data analysis of foals (n = 150) born from purebred brood mares of Thoroughbred, Arabs, and Percheron breeds (n1, n2, and n3 = 50 each) was made. Six hundred and twenty-four (n = 624) foals born between 2020 to 2022 were observed for the study of foal survival rate. The survival of these foals till the age of one year was considered. To study the growth and development of foals, height, bone, and girth measurements were taken at multiple developmental stages (3, 6, 9, 12, 15, and 18 months of age). Statistical analysis revealed that late-weaned foals demonstrated superior growth metrics compared to early-weaned foals (P = 0.001) and sheltered housing conditions markedly enhanced growth parameters across all breeds and measurement intervals (P = 0.002). However, no significant effect of season (P > 0.05) on the growth measurements across breeds was found. Arab and Thoroughbred breeds demonstrated significant early growth advantages in foals from middle-aged dams, with marked differences in height, bone width, and girth; however, by 15 months, these differences were not statistically significant (P > 0.05). In contrast, Percheron foals showed consistent growth regardless of the dam's age, suggesting breed-specific developmental influences (P = 0.885). Regarding the effects of extrinsic and intrinsic factors on foal survival, environmental conditions, and maternal age significantly impacted survival rates. Extreme winter conditions were associated with a notably lower survival probability (P = 0.002), and middle-aged dams exhibited significantly enhanced survival odds (P = 0.03). However, the influences of housing conditions and weaning age on survival were not statistically significant (P > 0.05), indicating these factors do not substantially affect foal survival within the first year. These results underscore the critical roles of weaning age, housing conditions, and age of dams in influencing foal growth and survival, highlighting the importance of tailored management practices in optimizing outcomes for the growth and development of young equines under subtropics.